ANALISIS KETERAMPILAN BERBICARA ANAK PANTI ASUHAN DALAM PEMEROLEHAN BAHASA KEDUA: KAJIAN SOSIOLINGUISTIK - Siti Halizah; Muhammad Masykur Baiquni (SulukAksara: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This study aims to analyze the speaking skills of children at the Taslimiyah Orphanage in the process of acquiring Indonesian as a second language from a sociolinguistic perspective. The focus of the study is directed at six components of speaking skills, namely fluency, pronunciation, intonation, vocabulary, grammar, and interaction, as well as the influence of the social environment on children's language use. This study uses a qualitative descriptive approach. Data were obtained through participant observation, informal interviews, and documentation of verbal interactions of children aged 5–10 years who were selected purposively. Data analysis techniques refer to the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions, with data validation through triangulation of sources and techniques. The results of the study indicate that children have been able to use Indonesian functionally in daily communication, although there are still limitations in aspects of pronunciation, sentence structure, and the tendency to code-switch with regional languages. Variations in speaking skills are influenced by age, intensity of interaction, and the multilingual social environment of the orphanage. The conclusion of this study confirms that the speaking skills of orphanage children reflect the process of second language acquisition which occurs naturally and contextually, and is greatly influenced by social factors and language habits in the surrounding environment.